2015
DOI: 10.1063/1.4933275
|View full text |Cite
|
Sign up to set email alerts
|

Ferroelectric modulation of terahertz waves with graphene/ultrathin-Si:HfO2/Si structures

Abstract: Ferroelectric-field-effect-tunable modulation of terahertz waves in graphene/Si:HfO2/Si stack structure was observed. The modulation shows distinct behaviors when the samples under different gate polarities. At a negative voltage, a transmission modulation depth up to ∼74% was present without depending on the photo illumination power, whereas, at a positive voltage, the modulation of Thz wave shows dependence on the illumination power, which is ascribed to the creation/elimination of an extra barrier in Si lay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…The interfacial barrier evolution under the inertial polarization filed and the external voltage field, respectively. Both energy hight and physical width of interfacial barrier were present under these internal and external filed 31 , 38 . Figure 1(c) shows the results of the XPS analysis on O 1 s spectrum in a-IGZO film.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…The interfacial barrier evolution under the inertial polarization filed and the external voltage field, respectively. Both energy hight and physical width of interfacial barrier were present under these internal and external filed 31 , 38 . Figure 1(c) shows the results of the XPS analysis on O 1 s spectrum in a-IGZO film.…”
Section: Resultsmentioning
confidence: 92%
“…HfO 2 with different oxygen (oxygen vacancy) content has ever been shown the surprising properties such as p-type conductivity 24 , luminescence 25 , ferroelectricity 26 , 27 , intrinsic d 0 magnetism 28 , excellent buffer function 29 and so on. Actually, we have also published several works about the ferroelectric behavior of highly oxygen-deficient HfO 2 dielectric films (OD-HfO 2 ) recently 30 , 31 . Highly oxygen-deficient state and/or dopant in HfO 2 films are the primary condition responsible for the formation of the ferroelectrical polarization, since this condition easily leads to lattice distortion to form ferroelectricity 32 .…”
Section: Resultsmentioning
confidence: 99%
“…Based on a similar working B,C) Reproduced with permission from Li et al 123 Copyright 2020, American Chemical Society mechanism, Jiang et al fabricated a modulator by embedded Si:HfO 2 into graphene film and Si substrate, which exhibited good modulation performance under both biasing directions. 122 It has been recently reported that coating gold nanoparticles (AuNPs) on graphene/silicon hybrid diode (Figure 5(B)) can further improve the modulation performance. 123 The localized surface plasmon resonance of AuNPs redistributes light-excited carriers near the interface.…”
Section: Heterostructurementioning
confidence: 99%
“…When the bias changed from 0 V to -4 V, the modulation amplitude depth became 83%. Based on this structure, Ran Jiang et al used a Si:HfO 2 material added between graphene and Si substrate to realize a device that had a modulation effect under both biasing directions [76]. However, it is more difficult to implement a hybrid modulation method since there are completely different responses when applying positive or negative biases.…”
Section: Thz Modulation Techniquementioning
confidence: 99%